Effects of Dietary Supplementation of Bovine Lactoferricin on Rumen Microbiota, Lactation, and Health in Dairy Goats - Shao, Yuexin; Zhang, Xian; Zhang, Huawen; Tian, Bowen; Weng, Yunan; Huang, Jiangtao; Lu, Christopher D.; Shi, Huaiping (Frontiers in Nutrition, 2021)
This study investigated the biological effects of supplementation of bovine lactoferricin at the rate of 100 mg/kg/d (LF-1) or 200 mg/kg/d (LF-2) in lactating dairy goats. Dietary bovine lactoferricin supplementation increased the content of lactoferricin in the milk and blood (p < 0.05) without affecting feed intake. In the LF-1 group, contents of serum Fe, total antioxidant content (T-AOC) and immunoglobulin A (IgA) were increased (p < 0.05), while malondialdehyde (MDA) were decreased (p < 0.05). In the LF-2 group, ruminal fluid pH were decreased (p < 0.05) and the composition of ruminal microflora on day 42 were more diversified. Firmicutes in LF-2 group was the most abundant phyla. In contrast, Bacteroidetes in the control and LF-1 were the most abundant. Lower milk somatic cell count and higher IgA content were observed in LF-1 and LF-2 than the control (p < 0.05). The observations suggested beneficial effects of supplementation of 100 mg/kg/d LFc on reducing oxidative stress and increasing diversity of ruminal microflora.